Role Of Women Leadership Attributes In Hospital Management - Punj, Divya (International Journal of Psychosocial Rehabilitation, 2019)
People all across the globe are affected by developments in the health care sector. Improvements in patient care, treatment follow-up, and other key aspects have contributed to the industry’s steady development throughout time. There has been progress for women in health care leadership, but there is still a long way to go before gender parity is achieved. In the past, women faced significant barriers to advancement in the health care industry. Despite ongoing efforts to level the playing field, women continue to face significant barriers to advancement in the medical profession. This imbalance of power is fascinating to consider since women are often the ones making choices about their health and the health care their families get. Women are heavily involved in the healthcare system as patients, yet they are underrepresented at the top levels of the sector.